2011
DOI: 10.1371/journal.pone.0015564
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Socioeconomic Position and Objectively Measured Physical Capability Levels in Adulthood: A Systematic Review and Meta-Analysis

Abstract: BackgroundGrip strength, walking speed, chair rising and standing balance time are objective measures of physical capability that characterise current health and predict survival in older populations. Socioeconomic position (SEP) in childhood may influence the peak level of physical capability achieved in early adulthood, thereby affecting levels in later adulthood. We have undertaken a systematic review with meta-analyses to test the hypothesis that adverse childhood SEP is associated with lower levels of obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
119
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(137 citation statements)
references
References 72 publications
(100 reference statements)
15
119
3
Order By: Relevance
“…As mentioned above, the cohorts demonstrate social inequalities from earlyto later-life stages, across a range of health indicators (5,20,41,42,75,77,108). They also provide some evidence for a link between health status and social mobility: Poor health is associated with downward mobility, and better health is associated with upward mobility (28,75 (75,77,103).…”
Section: Figurementioning
confidence: 67%
“…As mentioned above, the cohorts demonstrate social inequalities from earlyto later-life stages, across a range of health indicators (5,20,41,42,75,77,108). They also provide some evidence for a link between health status and social mobility: Poor health is associated with downward mobility, and better health is associated with upward mobility (28,75 (75,77,103).…”
Section: Figurementioning
confidence: 67%
“…Although SES in early life has been previously associated with adverse health and functional outcomes in later life, including poor physical performance [4][5][6]8,9], few studies have examined the associations between social adversity and physical performance in old age.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that economic disadvantage in childhood is associated with a range of adverse outcomes in adulthood, often independent of adulthood socioeconomic status [8,10,[24][25][26], suggesting that apparent current effects of economic adversity on health outcomes [5] may be a proxy for an accumulation of adverse exposures over a lifetime [6]. In addition to the effects of childhood economic adversity, we found a significant and graded association between childhood social adversity and poor physical performance, strongest in the most advantaged of our study sites, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations